2019
DOI: 10.1029/2019jg005262
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Vegetation Growth in the Urban Environment Across 32 Cities in the Northern Hemisphere

Abstract: How the urban environment influences vegetation phenology is important to understand the living environment and the climate‐vegetation interaction. This study investigates changes in vegetation phenology in the urban environment using remote sensing data for 32 major cities in the Northern Hemisphere. Vegetation phenological information for both urban and rural areas of each individual city was derived from the remote sensing data. We found that the urban environment generally enhanced vegetation growth but at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Similarly, Briber et al (2013) found that the GPP of Boston, MA, USA was ~75% lower than that of nearby Harvard Forest (HFR). However, there is evidence that tree and herbaceous plant growth rates are enhanced in urban areas worldwide, due to a combination of factors including elevated air temperature, atmospheric CO 2 , light availability, and nutrient availability (Briber et al, 2015; George et al, 2009; Pretzsch et al, 2017; Reinmann et al, 2020; Ruan et al, 2019; Searle et al, 2012; Sonti et al, 2019, Sonti, Griffin, et al, 2021; Zhao et al, 2016; Ziska et al, 2004). Despite enhanced growth rates, urban trees in some settings may not live as long as trees in rural forests (Smith et al, 2019), and fragmentation associated with urbanization may lead to increased climate stress (Reinmann & Hutyra, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Briber et al (2013) found that the GPP of Boston, MA, USA was ~75% lower than that of nearby Harvard Forest (HFR). However, there is evidence that tree and herbaceous plant growth rates are enhanced in urban areas worldwide, due to a combination of factors including elevated air temperature, atmospheric CO 2 , light availability, and nutrient availability (Briber et al, 2015; George et al, 2009; Pretzsch et al, 2017; Reinmann et al, 2020; Ruan et al, 2019; Searle et al, 2012; Sonti et al, 2019, Sonti, Griffin, et al, 2021; Zhao et al, 2016; Ziska et al, 2004). Despite enhanced growth rates, urban trees in some settings may not live as long as trees in rural forests (Smith et al, 2019), and fragmentation associated with urbanization may lead to increased climate stress (Reinmann & Hutyra, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to direct stress, elevated urban temperatures can also drive phenological shifts, with a potential cascade of negative effects (Fisogni et al 2020, Zipper et al 2016). Several studies have documented earlier owering in urban habitats for a range of plants including forbs, shrubs, and trees (Li et al 2017, Ruan et al 2019). However, a majority of these studies have been conducted using remotesensing techniques, which can give us a wealth of data on vegetative phenology a the macro-scale and have often focused on woody-plant communities.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf greening is an important attribute of vegetation throughout the growing season and is a basis for quantifying the water, energy, and carbon exchange between the atmosphere and the biosphere [262][263][264]. A special case analyzed in terms of the growing season transition dates is the impact of urban complexes.…”
Section: Introductionmentioning
confidence: 99%